CONCERNING THE SELECTION OF DESIGN AND TECHNOLOGY SOLUTION FOR A MINI-HOTEL CONSTRUCTION (Collection of scientific works «Modern structures of metal and wood», 2021)
The  article  considers  the  features  and  advantages  of  innovative  design  and technology solution for mini-hotels construction in the framework of eco-tourism development. The examination  of  the  main  potentials  of  eco-tourism  development  in  Ukraine  and  Moldova,  are presented on the example of the city of Tiraspol. Space planning and design features of the project "Dubovaya  Roshcha"  tourist  complex  in  Tiraspol,  Moldova  are  characterized  there.  This  article presents a method of multicriteria analysis of design and technology solutions based on the factor evaluation of decision options of low-rise building construction. In this examination the main factors influencing the choice of building structures were emphasized.